Pengaruh Beban Kerja, Disiplin Kerja Dan Kelelahan Terhadap Kinerja Karyawan Di PT XYZ - Salsabilla Harianto; Eka Mariyanti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This quantitative research was conducted on the employees of PT XYZ with the objective of examining the influence of workload, work discipline, and work fatigue on employee performance. Data were collected through questionnaires and interviews, with the study population consisting of all 74 employees of PT XYZ. The results of data analysis using SPSS (Statistical Product and Service Solutions) indicate that workload has a negative and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and work fatigue has a negative and significant effect on employee performance. Furthermore, workload, work discipline, and work fatigue simultaneously have a positive and significant effect on employee performance. Among these variables, work discipline is the most dominant factor influencing employee performance, contributing 26.9%.